A FARDA DO TENDEIRO: COTIDIANO E RECRUTAMENTO NO IMPÉRIO (Revista de História Regional, 2007)
The article narrates way as poors free man, in the paulista society in middle second the nineteenth century, faced and maked a certains attitudes ai-ming for to deal with unexpecteds the recruitemet for this National Guard.